The effect of sodium bicarbonate ingestion on 1500-m racing time - Bird, S. R.; Wiles, J.; Robbins, J. (Journal of Sports Sciences, 1995)
Twelve athletes, all of whom regularly participated in middle- or long-distance running races at club to national standard, competed in simulated 1500-m races under three conditions: following ingestion of 300 mg sodium bicarbonate per kg of body mass (B); following ingestion of a placebo (100 mg sodium chloride per kg of body mass and 200 mg calcium carbonate per kg of body mass) (P); and following ingestion of neither (C). A double-blind protocol was used between the B and P trials. Each condition was replicated so that the athletes competed in six races. Ten of the athletes completed all the races. The athletes' average times for trials B, P and C were 253.9, 256.8 and 258.0 s, respectively. The data were analysed using a two-way ANOVA with replicates and Tukey tests. This revealed a difference between trial B and trials P and C (P < 0.05), but no difference between trials P and C. These findings, therefore, indicate that sodium bicarbonate can have an ergogenic effect upon 1500-m running.